Organic Carbon Stocks of Mexican Montane Habitats: Variation Among Vegetation Types and Land-Use - Santini, Nadia S.; Villarruel-Arroyo, Alfredo; Adame, María Fernanda; Lovelock, Catherine E.; Nolan, Rachael H.; Gálvez-Reyes, Nancy; González, Edgar J.; Olivares-Resendiz, Betzabeth; Mastretta-Yanes, Alicia; Piñero, Daniel (Frontiers in Environmental Science, 2020)
Montane ecosystems occur throughout the world, and harbor many endemic species. They also provide key ecological services, including the catchment of water resources and the storage of organic carbon. These ecosystems are vulnerable to global climate change and increasing human pressures, including forestry and their conversion to arable land. In the extensive and biodiverse Mexican montane regions, ongoing deforestation and conversion to arable lands has led to diminished ecosystem health and services. Here, we undertook a comprehensive evaluation of carbon stocks within Mexican montane habitats in the Flora and Fauna Conservation Area of Nevado de Toluca. This aimed to integrate these habitats into Mexican and global census of forest carbon, the first step needed to convert on carbon credit markets to incentivise conservation of this region by local communities. Our study evaluated both, living biomass and belowground soil organic carbon in sites within forests, alpine grasslands and converted arable land. We addressed the following questions: (1) What are the organic carbon stocks, including the soil component, of our studied montane habitats? (2) What are the avoided CO2 emissions from maintaining natural forests and preventing conversion to arable land? And (3) Within our study area, are organic carbon stocks in the soil correlated to carbon stocks in aboveground living biomass? We found whole ecosystem organic carbon stocks ranged from 68 Mg OC ha-1 in unburnt alpine grasslands to 668 Mg OC ha-1 in Abies religiosa forests. By avoiding conversion of the Abies religiosa forests to arable lands, we show that emissions of 1,122 to 1,671 Mg CO2 ha-1 are avoided. Notably, the belowground soil organic carbon stock comprised ≥ 40% of the total ecosystem organic carbon stock. We recommend soil organic carbon stocks should be included within Mexican and global forestry carbon stock inventories, and should be considered within voluntary carbon-credit markets used to incentivize the conservation of Mexican montane habitats.